ANALYSIS OF EMPLOYEE RETENTION STRATEGY AT CV. dr. BL SKINCARE IN BEKASI, WEST JAVA - Lutam, Alin Michael; Saerang, David P.E; Rumokoy, Farlane S. (Universitas Sam Ratulangi, 2018)
Abstract: Such as the implementation of the strategy at CV dr BL Skincare that is not in accordance with existing work standards or standard operational procedure (SOP). This research aims to identify how the employee retention strategy at CV dr BL Skincare Bekasi, in West Java. Type of this research approach is descriptive with qualitative method is applied in this research since there will be observation and in-depth interview needed as a tool to gather data and analysis. The sample used saturated sampling method and only will be used in a small population such as employees and dr. Between Lutam as the owner at CV dr BL Skincare, which is there are 7 informants in this research in-depth interview. There are five indicator will be used in in-depth interview there are; Nature of Work, Remuneration, Flexible Working Hour, Team Relationship, and Job Security. The result employees at CV dr BL Skincare think that employee retention strategy in indicator remuneration is important there must be change. The strategy that being used situational salary at least up even if it does not follow UMP Bekasi West Java. From the result the researcher suggests are made the employees are not satisfied with their remuneration provided by the organization.Keywords: human resources, employee retention strategy